Cooperation in WTO’s Tariff Waters? - Nicita, Alessandro; Olarreaga, Marcelo; Silva, Peri (Journal of Political Economy, 2018)
This paper examines the extent to which tariff cooperation is observed among World Trade Organization members. With the help of a simple political economy model, we show that tariffs are positively correlated with the importer’s market power when they are set noncooperatively but negatively correlated when set cooperatively. We use this prediction to empirically identify the extent of cooperation in the WTO and find that more than three-quarters of WTO members’ tariffs are set noncooperatively.